Adjuvant chemotherapy and survival outcomes in rectal cancer patients with good response (ypT0-2N0) after neoadjuvant chemoradiotherapy and surgery: A retrospective nationwide analysis - Kuo, Yu-Hsuan; Lin, Yun-Tzu; Ho, Chung-Han; Chou, Chia-Lin; Cheng, Li-Chin; Tsai, Chia-Jen; Hong, Wei-Ju; Chen, Yi-Chen; Yang, Ching-Chieh (Frontiers in Oncology, 2022)
Background For rectal cancer, it remains unclear how to incorporate tumor response to neoadjuvant chemoradiotherapy (nCRT) when deciding whether to give adjuvant chemotherapy. In this study, we aim to determinate the survival benefit of adjuvant chemotherapy for rectal cancer patients with good response (ypT0-2N0) after nCRT and surgery. Methods The study cohort included 720 rectal cancer patients who had good response (ypT0-2N0) after nCRT and surgery, who did or did not receive adjuvant chemotherapy between January 2007 and December 2017, from the Taiwan Cancer Registry and National Health Insurance Research database. The Kaplan–Meier method, log-rank tests, and Cox regression analysis were performed to investigate the effect of adjuvant chemotherapy on 5-year overall survival (OS) and disease-free survival (DFS). Results Of 720 patients, 368 (51.1%) received adjuvant chemotherapy and 352 (48.9%) did not. Patients who received adjuvant chemotherapy were more likely to be female, younger (≤ 65), with advanced clinical T (3-4)/N (1-2) classification and ypT2 classification. No significant difference in 5-year OS (p=0.681) or DFS (p=0.942) were observed by receipt of adjuvant chemotherapy or not. Multivariable analysis revealed adjuvant chemotherapy was not associated with better OS (adjusted hazard ratio [aHR], 1.03; 95% Confidence Interval [CI], 0.88-1.21) or DFS (aHR, 1.05; 95% CI, 0.89-1.24). Stratified analysis for OS and DFS found no significant protective effect in the use of adjuvant chemotherapy, even for those with advanced clinical T or N classification. Conclusion Adjuvant chemotherapy may be omitted in rectal cancer patients with good response (ypT0-2N0) after nCRT and surgery.